P202 PRETREATMENT WITH ANTAGONISTS OF P2Y12 PLATELETS RECEPTORS IN ST–ELEVATION MYOCARDIAL INFARCTION: CLINICAL AND ANGIOGRAPHIC OUTCOMES. (18th May 2022) - Antonucci, A; Cutolo, A; Gallo, F; Bellin, A; Cavalli, G; Barbierato, M; Themistoclakis, S
Abstract: Background: The use of antagonists of P2Y12 platelets receptors as antiplatelets drugs is a cornerstone in the treatment of ACS. Many efforts are made to understand the right timing of beginning this therapy with the purpose to reduce intra– and periprocedural complications (stent thrombosis, no reflow phenomenon). The rationale behind "pretreatment" (administration of antagonists of P2Y2 platelet receptor before the coronarography) is valuable but the evidences are lacking, also in the setting of ACS–STEMI. Method and Objectives: We conduct an observational, monocentric (Ospedale dell'Angelo – Venezia Mestre), retrospective study including patients with STEMI (1st January 2016 – 9th august 2018). We compared two strategies of administration of clopidogrel, ticagrelor and prasugrel (pretreatment vs no pretreatment). Primary endpoints were bleeding BARC 3–5, acute or subacute stent thrombosis and TIMI flow grade > 0 in the culprit coronary. Secondary endpoints were cardiovascular and no cardiovascular in–hospital mortality and in–hospital neurological complications. Results: We studied 501 patients (199 in the group pretreated and 302 in the group no pretreated). The median time from first medical contact to PCI was 70, 5 minutes in the pretreated group and 60 minutes in the no pretreated group (p = 0.022). No significant differences between the two groups were observed in terms of acute or subacute stent thrombosis (OR 3.72 [0.82–14.20], p = 0.09) e TIMI flow grade > 0 in the culprit coronary (OR 1.11 [0.77–1.58], p = 0.58). In the multivariate analysis we observed that bleeding BARC 3–5 significantly were increased in the pretreated group (adjusted OR 2.78 [1.13–6.83, p = 0.025). In the subgroup analysis, the pretreated subjects with age > 75 were at augmented risk of bleeding BARC 3–5. Conclusions: Pretreatment in the setting of ACS–STEMI is not associated with benefits in terms of acute or subacute stent thrombosis and perfusion of culprit coronary but may cause clinically relevant bleedings, in particular in the elderly (age > 75).